Low‐Threshold, Highly Stable Colloidal Quantum Dot Short‐Wave Infrared Laser enabled by Suppression of Trap‐Assisted Auger Recombination. Issue 3 (18th November 2021) - Taghipour, Nima; Whitworth, Guy L.; Othonos, Andreas; Dalmases, Mariona; Pradhan, Santanu; Wang, Yongjie; Kumar, Gaurav; Konstantatos, Gerasimos
Abstract: Pb‐chalcogenide colloidal quantum dots (CQDs) are attractive materials to be used as tuneable laser media across the infrared spectrum. However, excessive nonradiative Auger recombination due to the presence of trap states outcompetes light amplification by rapidly annihilating the exciton population, leading to high gain thresholds. Here, a binary blend is employed of CQDs and ZnO nanocrystals in order to passivate the in‐gap trap states of PbS‐CQD gain medium. Using transient absorption, a fivefold increase is measured in Auger lifetime demonstrating the suppression of trap‐assisted Auger recombination. By doing so, a twofold reduction is achieved in amplified spontaneous emission (ASE) threshold. Finally, by integrating the proposed binary blend to a distributed feedback (DFB) resonator, single‐mode lasing emission is demonstrated at 1650 nm with a linewidth of 1.23 nm (0.62 meV), operating at a low lasing threshold of ≈385 μJ cm –2 . The Auger suppression in this system has allowed to achieve unprecedented lasing emission stability for a CQD laser with recorded continuous operation of 5 h at room temperature and ambient conditions. Abstract : A short‐wave infrared single‐mode laser is demonstrated based on PbS colloidal quantum dots (CQDs), which exhibit low threshold and highly‐stable performance owing to suppression of trap‐assisted Auger recombination at supra‐nanocrystalline level. PbS CQDs act as a gain medium where their trap states are electronically passivated by the donated electrons from ZnO nanocrystals.